PENGARUH POLA KOMUNIKASI GURU DENGAN SISWA TERHADAP AKTIVITAS BELAJAR SISWA PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 BASO - Genta Ilahi Pratama; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the extent of teacher communication with students so as to influence student learning activities in geography subjects at SMA Negeri 1 Baso. The type of research in this study is ex-post facto research with a quantitative approach. This research consists of two variables, namely the independent variable (X), namely the teacher's communication pattern with students and the dependent variable (Y) learning activity. The population in this study were all class X students at SMA Negeri 1 Baso who studied geography subjects totalling 251 students and a sample was drawn so that 71 students were obtained as respondents. Data collection is done by means of observation, questionnaires, and documentation. The data analysis techniques used are descriptive statistical analysis, simple regression, hypothesis testing, correlation analysis and the coefficient of determination. The results of this study indicate that one-way communication patterns are in the high category, two-way communication is in the medium category, many-way communication patterns are at the medium category level, and student learning activities are at the medium category level. Based on simple regression analysis, it can be concluded that there is a significant positive influence between teacher communication with students and learning activities in geography subjects at SMA Negeri 1 Baso.